Analysis of stresses and deformations of a cylindrical tank for natural gas vehicles - Alva Dávila, Fortunato (2006)
The present work tries on the analysis of efforts and deformations of cylindrical tanks for vehicular natural gas, using the analytic method studied by Lamé in 1833, verifying the results for numeric simulation by means of a commercial software (Cosmos Work) that is based in the application of the technique of finite elements and for the experimental method (strain gage). The study will allow formulating a calculation methodology and design of cylinders for vehicular natural gas, since; it is a high-priority necessity for our country, given the readiness of the natural gas of Camisea. At the moment, in the Peru, the technology about the production of the cylinders for discharges pressures has not still been developed. The lack of the methodology dedicated to the calculation and design of the cylinders, one of the reasons thathas motivated us the realization of this investigation work was. The cared cylinders have a very high cost, for that manifested it requires the local production to reduce them. In this context theanalytic methods are described, supported in the technique of the numeric simulation and later in the technique of the experimental method with the meter of deformations, to validate the analytic method and the existent Technical Norms that govern their design and production.